Using TOPSIS method with goal programming for best selection of strategic plans in BSC model - Dodangeh, Javad; Mohd Yusuff, Rosnah; Jassbi, Javad (Marsland Press, 2010)
Strategic planning is expressly significant for organization's success and competitive advantage making in an increasingly competitive business environment. Implementation of applicable strategies plays an important role for organizations' success. Balanced scorecard is a suitable tool for designing operative strategies. However, one of the balanced scorecard difficulties is the selection in strategic plans' performance. In this issue paper, was demonstrated a model for selection and ranking of strategic plans in Balanced Scorecard using Topsis method Goal Programming model. So first using the view and consensus of organization's managers and experts' opinions, measures of four perspectives and objectives are settled in BSC. And then using experts' opinions and taking the relative importance of decision makers' opinions into consideration, by using Goal Programming model and Topsis method, the implementations of strategic plans are selected in BSC model. The results are revealed that the introduced methods are more reliable and acceptable and the experts were verified the model for selecting of strategic plans in BSC in operation. The initiated methods were used in a study and derived results from it were analyzed from various points of view. In this article Initiative is called strategic plans.